Expressed emotion and psychological distress in caregivers of patients with an eating disorder. - Pérez-Pareja, Brígida; Quiles, Yolanda; Romero, Cristina; Pamies-Aubalat, Lidia; Quiles, Maria J. (Anales de Psicología / Annals of Psychology, 2013)
The main objective of this study was to evaluate the level of expressed emotion and psychological distress in caregivers of patients with an eating disorder, considering the differences in terms of sociodemographic and clinical characteristics. Fifty-three caregivers of patients with an eating disorder participed. The 39.6% of caregivers were men and 60.4% women, aged between 23 and 69 years old. The questionnaire used to assess expressed emotion was the Spanish version of the Level of Expressed Emotion (LEE) and for assessing distress the Spanish version of the Hospital Anxiety and Depression scale (HADS) and the General Health Questionnaire (GHQ-12). The results showed no statistically significant differences in expressed emotion in relation to the patient diagnosis and age of the caregivers. Significant differences were found regarding the type of relationship, the gender of the caregiver and illness duration; the caregivers with higher EE had more anxiety and depression than caregivers with lower EE.